NRGS13-003-0003. Socio Economic Impact of Shari’ah Compliant Hospitality Services for Malaysia and Muslim Communities - Mat Ghani, Gairuzazmi (2020)
This research study consists of six studies: 1. Input-output (IO) model which is the base for CGE model that is used to measure the impact of the proposed rating tools, legal and administrative mechanism of shari’ah compliant hospitality services. 2. Gravity model measuring the number and impact of tourist from OIC countries into Malaysia. 3. Gravity model measuring the destination and economics contribution of tourists from OIC countries. 4. Performance evaluation of Malaysian states in tourism services. 5. Performance evaluation of OIC countries in tourism services 6. Contribution of medical tourism to Malaysia’s economy.